Fully Distributed Multicast Routing Protocol for IEEE 802.15.8 Peer-Aware Communication - Woongsoo Na; Yunseong Lee; Jongha Yoon; Junho Park; Sungrae Cho (International Journal of Distributed Sensor Networks)
The IEEE 802.15.8 provides peer-aware communication (PAC) protocol for peer-to-peer infrastructureless service with fully distributed coordination. One of the most promising services in IEEE 802.15.8 is group multicast communication with simultaneous membership in multiple groups, typically up to 10 groups, in a dense network topology. Most of the existing multicast techniques in mobile ad hoc networks (MANET) have significant overhead for managing the multicast group and thus cannot be used for fully distributed PAC networks. In this paper, we propose a light-weight multicast routing protocol referred to as a fully distributed multicast routing protocol (FDMRP). The FDMRP minimizes routing table entries and thus reduces control message overhead for its multicast group management. To balance the control message, all nodes in the network have a similar number of routing entries to manage nodes in the same multicast group. To measure the effectiveness of the proposed FDMRP against the existing schemes, we evaluated performance by OPNET simulator. Performance evaluation shows that the FDMRP can reduce the number of routing entries and control message overhead by up to 85% and 95%, respectively, when the number of nodes is more than 500.